PRELIMINARY STUDY FOR THE IMPACT OF SCRATCH BLOCK CODING FOR SPECIAL NEED STUDENTS WITH HEARING DISABILITY - Wan Mohd Tarmizi Wan Mohd Yusuf; Mohd Muzammir Firdaus Abu Bakar (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
In the pursuit of modernizing and advancing high-tech implementation in daily life, it is essential for everyone to stay updated by learning how to use emerging technologies. While many children can learn about these technological developments in school, special needs students, such as those with hearing impairments, may face challenges. For these students to effectively use new mobile apps or computer programs, instructors must be capable of translating and explaining how to navigate and manipulate the technology. Scratch blocks programming offers a simple yet effective approach for beginners to learn programming through the intuitive action of dragging blocks containing preset code. This method is not only enjoyable but also highly effective in teaching hearing-impaired children basic programming concepts. Throughout the process, these students have shown positive responses in class and were able to follow the lessons. Teachers observed positive changes in cognitive skills by the end of the course. Our study evaluates the impact of Scratch block programming on the cognitive abilities of hearing-impaired students, using interviews with school teachers and observation during the learning session. The students’ engagement and progress during the lessons were notably positive, and cognitive improvements were clearly recognized by the teachers at the conclusion of the program.